Evaluation of the public health empowerment program in the Eastern Mediterranean region - Alsoukhni, Majd A.; Al Nsour, Mohannad; Alsouri, Ruba Kamal; Al Serouri, Abdulwahed; Hussain, Zakir; Annam, Labiba Saeed; Al Kohlani, Abdulhakeem; Khan, Mumtaz Ali; Samy, Sahar Mahmoud; ép Ben Alaya, Nissaf Bouafif; Abu-Khader, Ilham B.; Abbas, Haitham Bashier; et al. (Frontiers in Public Health, 2023)
Background: The Public Health Empowerment Program (PHEP) is a 3-month training program for frontline public health staff to improve surveillance quality and strengthen the early warning system capacities. Studies evaluating the program and its impact on the health systems in the Eastern Mediterranean Region (EMR) are lacking. Therefore, this study aimed to assess the level of PHEP graduates’ engagement in field epidemiology activities, assess their perceived skills and capacity to perform these activities and assess the extent to which PHEP helped the graduates to perform field epidemiology activities. Methods: A descriptive evaluation study was conducted based on levels 3 and 4 of Kirkpatrick’s model for evaluating training programs to assess the change in graduates’ behavior and the direct results of the program. Data were collected using two online surveys targeting PHEP graduates and programs’ directors/ technical advisers. Results: A total of 162 PHEP graduates and 8 directors/ technical advisers participated in the study. The majority of PHEP graduates reported that they are often involved in activities such as responding to disease outbreaks effectively (87.7%) and monitoring surveillance data collection (75.3%). High proportions of PHEP graduates rated their skills as good in performing most of field epidemiology activities. The majority of graduates reported that the PHEP helped them much in conducting, reviewing, and monitoring surveillance data collection (92%), responding effectively to public health events and disease outbreaks (91.4%), and communicating information effectively with agency staff and with the local community (85.2%). Conclusion: PHEP appears to be an effective program for improving the public health workforce’s skills and practices in epidemiological competencies in the EMR. PHEP strengthened the engagement of the graduates in most field epidemiology activities, especially during COVID-19.